The Influence of Family Function On The Quality of Life of Elderly People With Chronic Diseases - Syarifa Atika; Suraya Putri; Rahmawati (CV. Inara, 2026)
This study aims to analyze the influence of family function on the quality of life of elderly people with chronic diseases in Gampong Tanjung Selamat. This quantitative study used an observational analytical design through a cross-sectional approach. The study population was all elderly people suffering from chronic diseases in the area, with a sample of 29 respondents selected using a purposive sampling technique. The independent variable was family function and the dependent variable was the quality of life of the elderly. Data collection was carried out using a structured questionnaire that had been tested for validity and reliability, then analyzed univariately and bivariately using the Chi-Square test with a significance level of 0.05. Most respondents had good family function and good quality of life, and there was a significant influence between family function and quality of life of the elderly (p = 0.003). The better the family function carried out, the better the quality of life of the elderly with chronic diseases.